THE INFLUENCE OF PARENT PATTERNS ON SELF-TRUST OF PRIVATE SCHOOL STUDENTS - Khikmah Eny Wulansari (Universitas Pendidikan Indonesia, 2021)
Parenting style is something important for childhood. Because at that time it will shape the attitudes and emotions of children when they grow up. Self-confidence can be formed from parenting styles. The various parenting styles of the parents can make each child's self-confidence different. From research conducted since 2013-2021, it was found that the pattern of parenting that can make children's self-confidence high is democratic parenting. Meanwhile, authoritarian parenting will make children insecure. Here the researcher uses a Systematic Literature Review to be able to make conclusions from the overall research that has been made.